The increase of technical and economic efficiency of operation of thermal oil boilers - E. M. Rezanov (Омский научный вестник)
The advantages of thermal operation of thermal oil boilers are considered. An algorithm is proposed for determining the optimum air heating temperature required for burning fuel in boilers of petrochemical production, proceeding from the minimum of the total discounted costs for a recuperative device and burned fuel. The expediency of using the developed algorithm is substantiated, which makes it possible to reduce fuel consumption and increase the efficiency of a thermal oil boiler unit.